Synthesis and properties of anion conductive polymers containing dual quaternary ammonium groups without beta-hydrogen via CuAAC click chemistry. (16th July 2021) - Wu, Jianrong; Wei, Xiangtai; Jiang, Hao; Zhu, Yuanqin
Abstract: The preparation of anion exchange membranes (AEMs) with good performance still faces challenges. Herein, we present the synthesis of novel anion conductive polymers as AEMs from a newly designed side-chain precursor containing dual quaternary ammonium groups without beta-hydrogen via CuAAC click reaction. The resulting membranes exhibit good hydroxide conductivities in the range of 35.0–63.9 mS/cm at 80 °C. Moreover, the membranes show excellent alkaline stability with a high retention (>92%) in conductivity after immersed in 2 M NaOH at 80 °C for 480 h, and no obvious degradation was detected by NMR analysis. The DQ-PPO-17-OH membrane displays good fuel cell performance with a peak power density of 110 mW/cm under H2 /O2 at 60 °C. The results of this study may provide a valuable insight toward molecular designs to prepare high-performance AEMs by incorporating multiple quaternary ammonium groups without beta-hydrogen. Graphical abstract: Image 1 Highlights: A new side-chain precursor with dual QA groups without β-hydrogen was synthesized. DQ-PPO-x-I polymers were prepared from the precursor via CuAAC click chemistry. DQ-PPO-17-OH exhibits high alkaline stability and good single cell performance.